BMPR2 mutation status influences bronchial vascular changes in pulmonary arterial hypertension. Issue 6 (3rd November 2016) - Ghigna, Maria-Rosa; Guignabert, Christophe; Montani, David; Girerd, Barbara; Jaïs, Xavier; Savale, Laurent; Hervé, Philippe; Thomas de Montpréville, Vincent; Mercier, Olaf; Sitbon, Olivier; Soubrier, Florent; Fadel, Elie; et al.
The impact of bone morphogenetic protein receptor 2 ( BMPR2 ) gene mutations on vascular remodelling in pulmonary arterial hypertension (PAH) is unknown. We sought to identify a histological profile of BMPR2 mutation carriers. Clinical data and lung histology from 44 PAH patients were subjected to systematic analysis and morphometry. Bronchial artery hypertrophy/dilatation and bronchial angiogenesis, as well as muscular remodelling of septal veins were significantly increased in PAH lungs carrying BMPR2 mutations. We found that patients displaying increased bronchial artery remodelling and bronchial microvessel density, irrespective of the mutation status, were more likely to suffer from severe haemoptysis. History of substantial haemoptysis (>50 mL) was significantly more frequent in BMPR2 mutation carriers. 43.5% of BMPR2 mutation carriers, as opposed to 9.5% of noncarriers, displayed singular large fibrovascular lesions, which appear to be closely related to the systemic lung vasculature. Our analysis provides evidence for the involvement of the pulmonary systemic circulation in BMPR2 mutation-related PAH. We show that BMPR2 mutation carriers are more prone to haemoptysis and that haemoptysis is closely correlated to bronchial arterial remodelling and angiogenesis; in turn, pronounced changes in the systemic vasculature correlate with increased pulmonary venous remodelling, creating a distinctive profile in PAH patients harbouring a BMPR2 mutation. A distinctive pattern in hereditary PAH relating exuberant development of systemic lung vasculature to haemoptysis http://ow.ly/Iz2f303N1oN